论刘清韵戏曲中的性别意识 ：以新发现的两部剧本《拈花悟》和《望洋叹》为例 = Gender consciousness in Liu Qingyun's operas : the case study of two latest discovered scripts, Nian Hua Wu & Wang Yang Tan - 刘晓义 Liu, Xiaoyi (2010)
刘清韵（1842-1915年）生活在晚清动荡不安的时代，是历代女性戏曲家当中作品最多的一位。她其中的两部作品《拈花悟》和《望洋叹》于1990年被发现，但学术界对于这两部作品尚且缺乏比较系统的研究，尤其是针对其中值得关注的“性别意识”课题更是空白。本文拟以这两部作品为例，探讨刘清韵戏曲中的性别意识。首先，将梳理晚清女性戏曲创作的历史脉络，以及刘清韵作为一个女性作家的个人经历。接着，将分别对《拈花悟》和《望洋叹》进行文本细读，看看二剧分别创造的两个“单一性别世界”有着怎样的性别内涵。最后，将会对这两部作品进行全面地比较和总结，来探讨刘清韵戏曲当中展现出来的性别意识，包括如何实现对女性主体性的建构，如何展现对主流性别规范的反思和超越，如何使用折衷叙事的策略，提供性别超越的可能和期待。 Liu Qingyun (1842–1915) lived in the tumultuous late Ching era and was the most prolific female opera playwright in Chinese history. Two of her works Nian Hua Wu and Wang Yang Tan were discovered in the year 1990 but academia has yet to produce systematic research upon these two works. In particular, the subject of gender consciousness is of interest in her work but has received little attention. The following thesis examines gender consciousness as presented in Liu’s work with particular reference to these two newly discovered texts. The experiences of female playwrights in the late Ching era as well as Liu’s personal experiences as a playwright provide historical contexts from which to study her works.